Edukasi tentang Kesehatan Mental pada Remaja di SMK Soedirman Purbalingga - Dela Nataza Maharani; Noor Yunida Triana; Siti Haniyah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Mental health is an important aspect of adolescent development, as adolescence is a critical period marked by physical, emotional, and social changes. Adolescence is a process of self-discovery that begins around the age of 10 to 12 and ends between the ages of 18 and 22. Based on a preliminary survey conducted at SMK Soedirman Purbalingga Dusun II, Gandasuli, Bobotsari District, Purbalingga Regency on Thursday, July 18, 2024, it was found that there were 10 female students and 5 male students experiencing mental health issues. The objective of this Community Service (PkM) activity is to enhance teenagers' knowledge about mental health using methods such as lectures, discussions, and question-and-answer sessions. The media used include PowerPoint presentations and leaflets. The activity was conducted over 3 sessions attended by 30 students, with the results showing that teenagers' knowledge improved from an average score of 60 to 77. The PkM results showed that the average knowledge level before the education was 70% in the “adequate” category, which increased to 80% in the “good” category. Based on the Wilcoxon statistical test, the Z-value was -4.667 with a p-value of 0.000. The conclusion of the PkM is that it can enhance teenagers' knowledge through mental health education. Therefore, it is recommended to conduct further education by the school principal or school authorities to optimize future mental health development. The results of this community service were published in a community service journal and a poster.